The Structure and Stability of the Disulfide-Linked γS-Crystallin Dimer Provide Insight into Oxidation Products Associated with Lens Cataract Formation. Issue 3 (1st February 2019) - Thorn, David C.; Grosas, Aidan B.; Mabbitt, Peter D.; Ray, Nicholas J.; Jackson, Colin J.; Carver, John A.
Abstract: The reducing environment in the eye lens diminishes with age, leading to significant oxidative stress. Oxidation of lens crystallin proteins is the major contributor to their destabilization and deleterious aggregation that scatters visible light, obscures vision, and ultimately leads to cataract. However, the molecular basis for oxidation-induced aggregation is unknown. Using X-ray crystallography and small-angle X-ray scattering, we describe the structure of a disulfide-linked dimer of human γS-crystallin that was obtained via oxidation of C24. The γS-crystallin dimer is stable at glutathione concentrations comparable to those in aged and cataractous lenses. Moreover, dimerization of γS-crystallin significantly increases the protein's propensity to form large insoluble aggregates owing to non-cooperative domain unfolding, as is observed in crystallin variants associated with early-onset cataract. These findings provide insight into how oxidative modification of crystallins contributes to cataract and imply that early-onset and age-related forms of the disease share comparable development pathways. Graphical abstract: Unlabelled Image Highlights: Oxidized γS is dimeric with one inter- (C24) and two intramolecular disulfides (C22–C26). The dimeric structure is extended and is not perturbed relative to the monomer. γS dimer is stable at glutathione concentrations akin to aged and cataractous lenses. γS dimer exhibits non-cooperative unfolding and increased aggregation propensity. Oxidation of γS C22, C24, and C26 has been identified in age-related cataract lenses.